Guidelines for the treatment of malaria (World Health Organization, 2006)
Malaria is an important cause of death and illness in children and adults in tropical countries. Mortality, currently estimated at over a million people per year, has risen in recent years, probably due to increasing resistance to antimalarial medicines. Malaria control requires an integrated approach comprising prevention including vector control and treatment with effective antimalarials. The affordable and widely available antimalarial chloroquine which was in the past a mainstay of malaria control is now ineffective in most falciparum malaria endemic areas, and resistance to sulfadoxine-pyr